Simulations of a 2R robotic arm with MATLAB program - Tomozei, I; Bobe, A; Axinte, T (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Today, the simulation with MATLAB is a modern method to optimize a 2R robotic arm. One of the important problems of the 2R robotic arm is the mode of the rotation mode of his links. In the manuscript, an algorithm in MATLAB is proposed for the simulation of two bars that belong to a robot arm. However, the mechanism from this paper is composed of: links, joints, end effector and base. At the beginning the links are in a horizontal position. Furthermore, these links of the mechanism are programmed to counterclockwise rotate after 5 s, 8s and 10s. In finally, after 10s, the links of the system are in a vertical position.